Statistical study of environmental factors involved in incidence and emergence of blood cancers: retrospective clinical studies - Imani, Saber; Zand, Ali Mohammad; Borna, Hojjate; Panahi, Yunes; Salimian, Jafar; Saadat, Alireza; Ziaei, Robabeh; Hajihosseini, Saeedeh; Adib, Maryam; Fu, Junjiang (European Journal of Oncology and Environmental Health, 2015)
Aim of study: Blood cancers (BCs) are diseases that are hard to handle and can easily cause death. The statistics show that about 245,000 people have some form of BC. There are many factors affecting BC where preventing BC entails controlling these factors. The purpose of this retrospective study is to find which genetic and environmental risk factors in cancer have led to increased leukaemia over time. Materials and Methods: 762 patients with various BCs in haematology and oncology A and B sections of Shari’ati Hospital, who met the inclusion criteria, were enrolled in this retrospectively study from 2009- 2011. Patients’ information was collected using a researcher-made questionnaire from the moment patients arrived. Age, gender, ABO and Rh blood group, patient’s occupation, climate type (where patients live), Systolic and Diastolic Blood Pressure (SBP & DBP), Platelet (Plt) and hemoglobin (Hb) Count were carefully analyzed. Information questionnaires were processed in open source R software. Frequency and probability table, classification tree, correlations, χ2 and logistic regression, regression models were calculated so as to achieve a wide and clear perspective of impacting factors. A regression model was prepared and studied for possible influences. This study considered all probability less than 0.05 significant. Some factors were normalized or adjusted for data missing from questionnaires. Results: Results showed that the disease in men was 1.5 times higher than in women. Blood types (43%) along with positive Rh (76%) have the highest risk of BC. Low platelet count correlates more than 80% with BC. Patients who work in administration (32.7%) and services (28.7%) are more susceptible to leukaemia and most of the leukaemia patients were from warm dry regions (50.0%). The role of fatness in BC emergence is statistically ignorable. BC cases increase during the second decade of human life (48.7%), a fact which might be attributed to maturation processes. Conclusions: By due consideration of these environmental factors, we can make a proper evaluation of leukaemia and its prevention.